Strategi Penurunan Kecemasan Ibu Hamil Melalui Edukasi Kesehatan Mental - Jumrah Sudirman; Stang Stang; Suriani B (Institut Teknologi dan Bisnis Semarang, 2024)
Mental health issues in pregnancy are still considered less important than physical health. Mental health disorders are not yet seen as a disease. However, if not treated properly, the impact can be very serious and life threatening. Mental health disorders start with excessive worry which can lead to depression during pregnancy. Thus, if this situation persists, it can have a negative impact on the mother, baby, and family. One of the efforts to improve the mental health of mothers is through providing education to increase their knowledge. The purpose of this activity is to increase the knowledge and skills of mothers in maintaining mental health during pregnancy. The methods used were lectures, discussions and simulations. There were 12 participants involved in this activity. The results of the implementation of the activity showed an increase in knowledge in pregnant women after education, namely 75% of participants had knowledge with a good category in understanding about mental health during pregnancy.